ChemInform Abstract: Structure of Li4B2O5: High‐Temperature Monoclinic and Low‐Temperature Orthorhombic Forms. Issue 8 (1st March 2013) - He, Meng; Okudera, Hiroki; Simon, Arndt; Koehler, J.; Jin, Shifeng; Chen, Xiaolong
Abstract The structures of two Li4B2O5 polymorphs are determined by single crystal XRD and DFT calculations.